HPLC Based Metabolic Profiling of Rhizopus oryzae for Fumaric Acid Production Using Ammonia as a Neutralizing Agent - Shi, Chunzhen; Zhang, Hongman; Li, Shuang; Zheng, Hongbo; Xu, Qing; Huang, He (Asian Journal of Chemistry, 2013)
In a typical fumaric acid fermentation with Rhizopus oryzae, the presence of a neutralizing agent is required. In this work, metabolic profiling of R. oryzae for fumaric acid production by fermentation using ammonia as a neutralizing agent was carried out by HPLC. Principle component analysis was employed to classify HPLC data of R. oryzae fermentation. The variations of intracellular metabolites, i.e., cAMP, ATP, NADH and alanine were measured by HPLC. The results showed fumaric acid production by fermentation with R. oryzae using ammonia as a neutralizing agent can be divided into two phases: the former fermentation phase and the latter fermentation phase. ATP, NADH, cAMP and alanine were the biomarkers. ATP, NADH, cAMP positively correlated to fumaric acid yield, whereas alanine had negative correlation to fumaric acid yield.